#TITLE_ALTERNATIVE# - NGURAH SATRIYADI H. (NIM 23298033); Pembimbing : Ngapuli Irmea Sinisuka, Dr. Ir., I.G.
Abstract : Maintenance scheduling for electrical equipment such as power transformers is needed to get an effective and efficient operation in given condition. This scheduling can be analyzed by mathematical approach based on availability and reliability performance of power transformer operation. The effective and efficient maintenance scheduling can eliminate unnecessary operation costs. Markov model application for maintenance scheduling evaluation on power transformers insulation oil applied in switchgears and the state conditions determined by electrical isolation deterioration on transformer oil are presented This model consists of states that probably happen on power transformers, and it includes transitions among states that describe every probability rate. Modeling needs more specific criteria for each state that can happen. Simulation results give the steady-state availability performance and reliability performance for power transformers for different scheduling period given. Availability and Reliability curves can be used as parameter to decide effectiveness and efficiency of maintenance scheduling.